2006
DOI: 10.1111/j.1600-0501.2006.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of new bone during vertical distraction osteogenesis of the human mandible is related to the presence of blood vessels

Abstract: We examined the effect of distraction rate on blood vessel growth in intramembraneous ossification after vertical distraction osteogenesis in the human mandible. Six edentulous patients (aged 60+/-9 years) with a severely atrophic mandible underwent bone augmentation with distraction osteogenesis. Two distraction rates (0.5 and 1 mm/day) were compared and for each group three patients were analyzed. Vascular histomorphometry was carried out in two different areas in the distraction gap: (1) in the first and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Three-dimensional observation is possible without destruction of the specimen using micro CT (Odgaard 1997). Some studies have adopted two-dimensional morphometrical parameters for DO (Zimmermann et al 2005;Amir et al 2006), but it has not been confirmed three-dimensionally. Our morphometrical observations that remodeling is delayed without periosteum are in line with the CLSM findings that bone remodeling was sparse during the latter half period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three-dimensional observation is possible without destruction of the specimen using micro CT (Odgaard 1997). Some studies have adopted two-dimensional morphometrical parameters for DO (Zimmermann et al 2005;Amir et al 2006), but it has not been confirmed three-dimensionally. Our morphometrical observations that remodeling is delayed without periosteum are in line with the CLSM findings that bone remodeling was sparse during the latter half period.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, excessive elongation (overcorrection) is an actual solution as many reports point out (Saulacic et al 2005;Kanno et al 2006;Ettl et al 2009). Secondly, the distraction rate is an important condition, and it has been indicated that frequent distraction was more effective for good bone formation (Zimmerman et al 2005;Amir et al 2006). Thirdly, combination of growth factors may be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22][23] More recent studies have also demonstrated bone regeneration in human jaws in conjunction with optimal distraction protocols. 24,25 The aim of this review is to present current knowledge of bone formation during distraction osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Angiogenesis include migration, proliferation and differentiation of endothelial cells for new capillary from the existing vessels. Firstly, vascularization delivers oxygen for osteoblasts metabolic activity.…”
Section: Introductionmentioning
confidence: 99%